Agenda: Ormond Beach Task Force - California State Coastal Conservancy (California State Coastal Conservancy)
Agenda of 10 topics to be covered including: wetland restoration plan, land preservation status, EPA & Halaco, pollution prevention, and snowy plover & least tern recovery program.